Dynamic of Bacterial and Phage Populations Maintained in Chemostat System with Dilution Control Parameter - Aluf, Ofer (Discoveries in Agriculture and Food Sciences, 2016)
In this article, we discuss the crucial subject of bacteria and phage populations dynamic in chemostat system with dilution control parameter. A chemostat (from chemical environment is static) is a bioreactor to which fresh medium is continuously added, while culture liquid is continuously removed to keep the culture volume constant. By changing the rate with which medium is added to the bioreactor the growth rate of the microorganisms can be controlled. In chemostat model, the control parameters usually are the washout rate (dilution rate D) and input nutrient concentration S(0). We consider that S(0) is fixed and D is the only control parameter. The outputs considered in chemostat models are functions: £: R3 → Rk (k ≤ 3) of variables S(t); V (t) and B(t). The dynamical behavior of chemostat system with control tools is inspected and stability analysis is done. The chemostat system with dilution control parameter can be represented as differential equations, depending on variable and parameters. First the system is analyzed for zero talent period (T= 0) and secondly for positive value of talent period (T > 0).